A Meta-Analytic Investigation of the Relationship Between State Affect, Discrete Emotions, and Job Performance. - Shockley, KristenM.; Ispas, Dan; Rossi, MichaelE.; Levine, EdwardL. (Human Performance, 2012)
The relationship between affect and job performance has been the topic of previous meta-analytic investigations. However, these studies have been limited by their focus on only one form of affect, trait dimensional affect, or failure to differentiate between various forms of affect, such as state affect and emotions. The present study extends past research by meta-analytically examining the association between state dimensional affect and discrete emotions and three dimensions of job performance, task performance, organizational citizenship behavior, and counterproductive work behavior. In addition, we examined subgroup differences according to the temporal consistency of performance and affect measurement, and we reviewed studies that assessed the affect–performance link using within-person analyses in the context of experience sampling designs.